Role of acoustic radiation force impulse imaging elastography in the assessment of steatohepatitis and fibrosis in rat models. (September 2018) - Guo, Yanrong; Lin, Haoming; Dong, Changfeng; Zhang, Xinyu; Wen, Huiying; Shen, Yuanyuan; Wang, Tianfu; Chen, Siping; Liu, Yingxia; Chen, Xin
Highlights: Accurate assessment of NASH is important in patients with NAFLD. The diagnostic performance for staging fibrosis in patients with NAFLD is potentially affected by several factors such as hepatic steatosis, inflammation, and ballooning. This study finds that ARFI elastography is a promising method for differentiating non-NASH rats from NASH rats and for staging hepatic fibrosis with NASH. This study also finds that the presences of severe steatosis and severe lobular inflammation have significant impacts on assessing fibrosis stages, respectively. Abstract: Acoustic radiation force impulse (ARFI) elastography is a non-invasive method for performing liver assessment via liver shear wave velocity (SWV) measurements. The aim of this study was to evaluate the performance of the ARFI technique in the diagnosis of nonalcoholic steatohepatitis (NASH) and fibrosis and to investigate the effect of steatosis and inflammation on liver fibrosis SWV measurements in a rat model of nonalcoholic fatty liver disease (NAFLD). The ex vivo right liver lobes from 110 rats were processed and embedded in a fabricated gelatin phantom, and the other lobes were used for histologic assessment. The SWV induced by acoustic radiation force was derived to evaluate liver stiffness. The experimental results showed that the liver SWV value could be used to differentiate non-NASH rats from NASH-presenting rats and NASH from cirrhosis, and these comparisons showed areas under the receiver operating characteristic curves (AUROC) of 0.951 and 0.980, respectively. The diagnostic performances of ARFI elastography in predicting severe fibrosis ( F ≥ 3) and cirrhosis ( F ≥ 4) showed AUROC values of 0.997 and 0.993, respectively. In rats with mild fibrosis (F0–F1), severe steatosis had a significant effect on the mean SWV values. In rats with significant fibrosis (F2–F4), severe lobular inflammation had significant effects on the mean SWV values. Our findings indicate that ARFI elastography is a promising method for differentiating non-NASH rats from NASH rats and for staging hepatic fibrosis in NASH. The presence of severe steatosis and severe lobular inflammation are significant factors for evaluating fibrosis stages.